PENGARUH POLA ASUH ORANG TUA TERHADAP DISIPLIN BELAJAR SISWA - Novitalia Novitalia; Umbu Tagela; Yustinus Windrawanto (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Adolescence is a transitional period from childhood. Adolescence is marked by the search for identity, then in adulthood self is obtained little by little absorbed in the order of chronological age and spiritual age. This study aims to determine the effect of parenting style on the learning discipline of class XI students of the Fashion Design Department of SMK Negeri 1 Bancak. The approach in this study is a quantitative approach with comparative causal methods. The sampling technique used in this study was total sampling, so that the sample in this study amounted to 72 students of class XI, the Department of Fashion. Data collection tool using a questionnaire. Based on the results of the descriptive analysis, it was stated that the majority of parents applied permissive parenting with a percentage of 40.3%, and student learning discipline was in the sufficient category with a percentage of 53.8%. Based on simple linear regression analysis, it is stated that there is a significant effect of parenting style on student learning discipline, where parenting style has a contribution of 11.1%